PERANCANGAN PANEL SURYA MENGGUNAKAN TRANSISTOR (2N3055 & MJ2955) DENGAN EFEK PANTUL SINAR MATAHARI UNTUK OPTIMASI ENERGI LISTRIK YANG DIHASILKAN - Venny Yusiana; Hendi Matalata (Jurnal Civronlit Unbari, 2018)
Solar or solar energy can be an alternative source of energy in the future, where solar energy can be converted into electrical energy by utilizing the photoelectric effect that occurs in photovoltaic components or solar cells.  Solar cells or photovoltaic components can convert sunlight into electrical energy that can be used directly by the load or stored in a battery, a kind of electrochemical device that can store electrical charges in the form of chemical energy. The electrical energy generated by the solar cell is influenced by the intensity of light received by the sun. To gain the desired power and voltage, the solar cells are connected in series and parallel into a solar cell module. 2N3055 & MJ2955 transistor based solar panels are the basic materials for designing alternative power generation. In the process of manufacture, this solar panel utilizes the components of used components that are still feasible to use, so it can be used to be the appropriate technology to produce a solar panel that utilizes solar energy in the form of sunlight and solar heat. In this study also conducted experiments using glass components as a reflection effect from light sources. The result of this experiment obtained that the amount of electrical energy output resulting from the reflection effect of light by using 2N3055 transistor and MJ2955 transistor can produce increased current and increase electrical power.Keywords: Solar cell, Transistor 2N3055 & MJ2955, The effect of reflection light